Nitrogen Addition and Arbuscular Mycorrhizal Fungi Beta Diversity: Patterns and Mechanisms - Lu, Yawen; Liu, Xiang; Zhou, Shurong (Frontiers in Environmental Science, 2021)
Global nitrogen eutrophication, which is disrupting the intimate plant–arbuscular mycorrhizal fungi (AMF) symbiosis, can alter the diversity and physiological functions of soil AMF greatly. However, shifts of beta diversity and the intrinsic patterns of AMF community dissimilarities in response to nitrogen addition remain unclear. Based on a 7-year nitrogen addition experiment in a Qinghai–Tibet Plateau alpine meadow, we detected the changes in soil AMF alpha diversity (richness and genus abundance) and the community composition beta diversity by partitioning the two components of Simpson and nestedness dissimilarities along (turnover) and within (variation) nitrogen addition treatments, and fitted with environmental factor dissimilarities. We found that nitrogen addition decreased AMF richness by decreasing the most dominant AMF genus of Glomus but increasing the abundance of the rare genera. The turnover of the AMF community overall beta diversity along the nitrogen addition gradients was induced by the increased nestedness dissimilarity, while the variation within treatments was explained by both increased Simpson and nestedness dissimilarities, which was significantly correlated with soil pH. Our study found both Simpson and nestedness dissimilarities worked on the AMF community dissimilarity after nitrogen addition and the significant variation within the same treatment, which would be important in the future for predicting global AMF or microbial diversity changes in response to nitrogen eutrophication.